Modern Management Methods and Trends of Changes in Organizations During the Crisis and Pandemic - Jerzy WACHOL (Communications of International Proceedings, 2021)
The study presents changes in the global economy affecting the development of enterprises, taking into consideration modern methods of management, process management and sustainable development in the times of the pandemic and crisis. It depicts transmissions of economic effects in the world caused by big corporations. It analyses selected aspects of development of enterprises in theoretical terms and in the global surrounding, taking into account ecology and modern management concepts. Research problem: modern management methods in the face of the pandemic and crisis. Major findings: currently, marketing, finance, profit, strategies, HR, innovativeness, modern management methods, forms of organisation, etc. play an important role in enterprises. On the other hand, IT elements already have an important and increasing position, especially in the face of the pandemic, remote work and global crisis. Using statistical methods, based on collected statistical socio-economic data as well as surveys and own studies, conclusions regarding modern management methods of trends of changes in organisations in the face of the pandemic and crisis were drawn.
Keywords: Management concepts; process management; organisation surroundings; sustainable development; corporate supervision; globalisation.